Endothelin-1 in the tumor microenvironment correlates with melanoma invasion. Issue 3 (June 2016) - Chiriboga, Luis; Meehan, Shane; Osman, Iman; Glick, Michael; de la Cruz, Gelo; Howell, Brittny S.; Friedman-Jiménez, George; Schneider, Robert J.; Jamal, Sumayah
Abstract : Endothelin-1 (ET-1) is a vasoactive peptide that also plays a role in the tanning response of the skin. Animal and cell culture studies have also implicated ET-1 in melanoma progression, but no association studies have been performed to link ET-1 expression and melanoma in humans. Here, we present the first in-vivo study of ET-1 expression in pigmented lesions in humans: an ET-1 immunohistochemical screen of melanocytic nevi, melanoma in situ lesions, invasive melanomas, metastatic melanomas, and blue nevi was performed. Twenty-six percent of melanocytic nevi and 44% of melanoma in situ lesions demonstrate ET-1 expression in the perilesional microenvironment, whereas expression in nevus or melanoma cells was rare to absent. In striking contrast, 100% of moderately to highly pigmented invasive melanomas contained numerous ET-1-positive cells in the tumor microenvironment, with 79% containing ET-1-positive melanoma cells, confirmed by co-staining with melanoma tumor marker HMB45. Hypopigmented invasive melanomas had reduced ET-1 expression, suggesting a correlation between ET-1 expression and pigmented melanomas. ET-1-positive perilesional cells were CD68-positive, indicating macrophage origin. Sixty-two percent of highly pigmented metastatic melanomas demonstrated ET-1 expression in melanoma cells, in contrast to 28.2% of hypopigmented specimens. Eighty-nine percent of benign nevi, known as blue nevi, which have a dermal localization, were associated with numerous ET-1-positive macrophages in the perilesional microenvironment, but no ET-1 expression was detected in the melanocytes. We conclude that ET-1 expression in the microenvironment increases with advancing stages of melanocyte transformation, implicating a critical role for ET-1 in melanoma progression, and the importance of the tumor microenvironment in the melanoma phenotype.